RESEARCH ON THE MEASUREMENT SYSTEM FOR FLEXIBLE JOINT’S PIVOT POINT DRIFT BASED ON MACHINE VISION - WEN YueBing; TAN JianPing; WANG Xian; LI KaiMo (Jixie qiangdu)
A certain measurement system for flexible joint’s pivot point drift has been studied in this paper. The detection system consists of camera bracket,signposts,image processing module,pivot point calculation module,result processing module,industrial camera,data interface,industrial computer and some other auxiliary devices. Two signposts are fixed on the line at a certain angle to the center line of the swinging body to be measured. When the signposts swing together with the swinging body,the industrial camera will take continues samples from it. Then the samples will be transferred to the industrial computer by the data interface. After that the image processing module will get the signposts ’position in the measurement system plane coordinates by images denoising, background subtraction and signposts positioning. With this information the pivot point calculation module will calculate the average pivot point of two different samples to approach the momentary pivot position while the swinging body swings according to the mathematic model. The result processing module will record and visualize the pivot point movement trajectory. The precision of this measurement system is about 0. 5% which has been checked by simulation and proved by test.